The Involvement of Women in Tourism Village of Pujon Kidul, Malang, Indonesia - Rita Parmawati; Wike Wike; Edriana Pangestuti (Journal of Indonesian Tourism and Development Studies, 2019)
Pujon Kidul Village has succeeded in tourism village, that improving the economy and social life and women's participation was seen in the technical sphere. It is interesting to analyze how women have played a role in a tourism village. This study aims to identify internal and external factors that support women's participation, identify the level participation, and analyze contributions to household income. We establish operational definitions in the form of internal and external factors and analyzed using cross tabulation and then Rank Spearman non-parametric statistical tests to provide an overview of study boundaries and data retrieval procedures. There are 56.7% of women who are graduating from high school/university and 173.33% have been in the tourism business for more than 5 years. Internal factors that have a significantly weak relationship are the level of women's education. Meanwhile, the aspect of the relationship between women's education level and women's participation as business actors in tourism villages was 100 percent in the low and medium categories, and 90 percent are in the high category. The influence of community actors to women participation is very high (100%). There are 53.57% of women had a high level of participation and contribution to household income.Keywords: Involvement, Pujon Kidul, Village tourism, Women.